Formation of innovative type of employment - Tazhbayev, A.M.; Aimagambetov, E.B.; Kapelyuk, Z.A. (BUKETOV BUSINESS REVIEW, 2021)
Object: To consider theoretical and methodological approaches to the formation of innovative-type employment of the population. Methods: Comparative analysis methods were used during the study. Results: The article defines the interaction of factors of innovative and technical development in the formation of innovative type of employment. The result of the introduction of innovations in production is the predominance of people with a high level of education and professional qualifications in the labor market, which, in turn, forms an innovative type of employment of the population. Conclusions: The state policy today is aimed at supporting the employment of the population by implementing the main directions according to the state and regional programs in order to prevent social tension in society. State institutions need to develop a regional employment policy aimed at increasing intellectual potential, developing an innovative environment, and activating employment in an innovative economy.